De la negociación al conflicto: la transformación de la relación Ejecutivo-Legislativo en México, 2018-2024 - Velázquez López Velarde, Rodrigo; González Viveros, Liliana Deyanira (El Colegio de México A.C., 2025)
From Mexico’s democratic transition in 1997 until 2018, presidents without a legislative majority were forced to negotiate their agenda with the opposition or adjust it, based on their political party support in Congress, thus maintaining a relative balance between the Executive and Legislative branches. With the arrival to power of Andrés Manuel López Obrador (AMLO), who implemented a direct confrontation strategy with the opposition, the balance was broken, weakening institutional checks and balances. Based on a comparative analysis of constitutional review actions (acciones de inconstitucionalidad) during the Peña Nieto and AMLO administrations, we identify three specific actions through which this conflict strategy was carried out and eventually transformed the Executive-Legislative relationship: the use of undemocratic Legislative procedures by the ruling coalition to pass key presidential initiatives; the approval of reforms aimed at weakening institutional checks and balances; and the opposition’s challenges of major reforms in the Supreme Court. The analysis reveals that the political conflict strategy hindered the potential cooperation between the branches of power and undermined fundamental components of the democratic system.